A novel model for image classification based on Persistent Homology - Petar Sekuloski; Dimitrievska Ristovska, Vesna; Vassil Grozdanov (International Journal of Science and Research (IJSR), 2022)
Topological Data Analysis (TDA) is relatively new field of Applied Mathematics that emerged rapidly last years. The main tool of Topological Data Analysis is Persistent Homology. Persistent Homology tracks the topological features of datasets. In this paper we will introduce a novel model for image classification based on Persistent Homology. In the experimental part we the introduced new novel on real medical dataset. Using this model, the classification was improved.
Keywords: Topological Data Analysis, Persistent Homology, Machine Learning, Computational Topology, Image Classification